2015
DOI: 10.1016/j.mayocp.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Long Survival and Severe Toxicity Under 5-Fluorouracil–Based Therapy in a Patient With Colorectal Cancer Who Harbors a Germline Codon-Stop Mutation in TYMS

Abstract: We report the first clinical description of a patient with cancer with a heterozygous germline codon-stop mutation in the TYMS gene. The mutation g.657795_657826del, c.53_84del (NM_001071.2), p.Gln18Argfs*42 causes loss of function of one of the TYMS alleles, resulting in a truncated protein. This gene codifies for the target enzyme of 5-fluorouracil (5-FU), the basic treatment in colorectal cancer. The patient, diagnosed with metastatic colorectal cancer, had diarrhea and neutropenia grade 4 and mucositis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…TYMS is an essential enzyme involved in DNA replication and repair, which serves an important role in the biosynthesis of deoxythymidine monophosphate (dTMP) (17). The association between TYMS and tumors has been reported previously.…”
Section: Discussionmentioning
confidence: 90%
“…TYMS is an essential enzyme involved in DNA replication and repair, which serves an important role in the biosynthesis of deoxythymidine monophosphate (dTMP) (17). The association between TYMS and tumors has been reported previously.…”
Section: Discussionmentioning
confidence: 90%
“…Wnt signaling pathway, well-known functioning in the process of tumorigenesis, contributed to development, progression and metastasis of various cancers (MacDonald et al, 2009). Thymidylate synthase (TYMS), a key enzymes of 5-fluorouracil (5-FU) catabolic pathway, had been correlated with 5-FU-based therapy (Balboa-Beltran et al, 2015). Furthermore, as a result of TYMS depletion caused by miR-197, the sensitivity to 5-FU was increased .…”
Section: Mir-197 In Drug Resistancementioning
confidence: 99%
“…The mutations in TYMS (g.657795_657826del, c.53_84del and p.Gln18Argfs*42) were reported to connect with survival of CRC 24 . A meta-analysis conducted by Jennings BA et.al 25 suggested that TYMS rs45445694 was associated with the reduced protein expression and improved clinical benefit from 5-FU.…”
Section: Discussionmentioning
confidence: 99%